Preparation and application of flexible aerogel electroencephalogram electrode

CN117801376BActive Publication Date: 2026-10-20CHONGQING SCI & INNOVATION CENT OF NORTHWEST POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311518579.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2026-10-20
Estimated Expiration
2043-11-15

AI Technical Summary

Technical Problem

[0006]本发明的目的在于解决现有银纳米线掺杂导电聚合物在成型时容易在聚合物基质中团簇以及银纳米线容易被氧化的技术问题,而提供了一种柔性气凝胶脑电电极的制备及应用

Benefits of technology

[0042]1.本发明一方面在银纳米线表面包覆聚吡咯(PPy)涂层,不仅可以隔绝氧气,减缓氧化过程,提高银纳米线的结构稳定性(AgNWs在氧化环境下稳定性很差,结构会遭到破坏),还可以减少银纳米线之间的相互粘连,避免形成团簇,同时,PPy涂层还有利于提高导电性;如此制备了聚吡咯包裹银纳米线。另一方面,由醋酸纤维素制成三维气凝胶网络,通过搅拌使聚吡咯包裹银纳米线在整个气凝胶网络中均匀分布,以提高电导率,降低与人体间的接触阻抗。该方法在完美解决银纳米线掺杂导电聚合物在成型时易团簇易氧化问题的同时,具备柔性、抗菌性、保湿性以及高导电性,通过此方法制备的聚吡咯包裹银纳米线掺杂的气凝胶电极在可穿戴设备等新兴产业领域有着良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117801376B_ABST
    Figure CN117801376B_ABST
Patent Text Reader

Abstract

The application provides preparation and application of a flexible aerogel electroencephalogram electrode, and solves the technical problems that silver nanowire doped conductive polymers are easy to cluster in a polymer matrix and silver nanowires are easy to be oxidized during molding. In one aspect, a polypyrrole coating layer is coated on the surface of the silver nanowire, which can not only isolate oxygen, slow down the oxidation process, improve the structural stability of the silver nanowire, but also reduce the mutual adhesion between the silver nanowires, so as to avoid the formation of clusters. Meanwhile, the PPy coating layer is also conducive to improving the conductivity. In another aspect, a three-dimensional aerogel network is made of cellulose acetate, and the polypyrrole is wrapped around the silver nanowire and uniformly distributed in the entire aerogel network through stirring, so as to improve the conductivity and reduce the contact impedance between the human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to the preparation and application of a flexible aerogel electroencephalogram (EEG) electrode. Background Technology

[0002] Currently, commercial electrodes, such as gold cup electrodes and Ag / AgCl electrodes, can only have conductive adhesive coated on their surface. As the conductive adhesive loses water, the signal acquisition quality rapidly declines, which is not conducive to long-term use. Furthermore, they lack consideration for user comfort, antibacterial properties, biocompatibility, and other electrode safety and lifespan considerations. Aerogels have emerged to address these issues.

[0003] Aerogels are three-dimensional polymer network systems composed of polymers, possessing excellent biocompatibility, lightweight, and porous properties, making them valuable for a wide range of applications. Among them, conductive aerogels have attracted widespread attention in recent years due to their potential in flexible electronics, sensors, and other fields. Extensive research has been conducted on conductive aerogels based on various conductivity principles, resulting in significant progress.

[0004] Among various conductive aerogels, metal-based conductive aerogels are widely used due to their high conductivity and ease of preparation. Silver nanowires, as one of the commonly used metal nanomaterials in conductive aerogels, possess excellent electrical conductivity, ultra-high stretchability, and sensing sensitivity. When silver nanowire-doped aerogels are stretched, energy can be dissipated on the uniformly distributed silver nanowires, reducing internal stress and thus improving the mechanical properties of the aerogel material. However, silver nanowires have poor dispersion and are incompatible with the polymer matrix (i.e., the matrix material used to prepare the aerogel). During the stretching and molding of the aerogel, stress is concentrated on the aggregated (i.e., clustered) silver nanowires, accelerating the failure process of its mechanical properties (stretching or compressing ability). In addition, the surface of silver nanowires is easily oxidized, leading to a decrease in conductivity, which also reduces the long-term lifespan of the device.

[0005] In view of the above problems, the research team of this invention needs to optimize the gel preparation of silver-doped nanowires. Summary of the Invention

[0006] The purpose of this invention is to solve the technical problems of existing silver nanowire-doped conductive polymers being prone to clustering in the polymer matrix during molding and silver nanowires being easily oxidized, and to provide a flexible aerogel EEG electrode preparation and application.

[0007] To achieve the above-mentioned objectives, the technical solution provided by this invention is as follows:

[0008] A polypyrrole-coated silver nanowire-doped aerogel is characterized by comprising a three-dimensional aerogel network obtained by physical cross-linking of cellulose acetate through static interaction, and polypyrrole-coated silver nanowires uniformly doped in the three-dimensional aerogel network.

[0009] The average width of the silver nanowires is approximately 80-200 nm, while the average width of the polypyrrole-coated silver nanowires is 200-400 nm; the thickness of the polypyrrole coating is 120-200 nm. Longer and thicker silver nanowires facilitate interconnection after doping, improving conductivity. At this size, interconnection is also more efficient, reducing impedance.

[0010] The method for preparing the above-mentioned polypyrrole-encapsulated silver nanowire-doped aerogel is characterized by comprising the following steps:

[0011] 1) Preparation of polypyrrole-coated silver nanowires

[0012] 1.1) Disperse Ag NWs in a mixed solution of water and ethanol, and mix and stir with pyrrole (Py) monomer at room temperature;

[0013] 1.2) Add AgNO3 solution to the mixed solution obtained in step 1.1), continue stirring for 3-6 hours, and then let stand for at least 24 hours;

[0014] 1.3) After the reaction is complete, filter and wash the precipitate to obtain polypyrrole-encapsulated silver nanowires AgNWs@PPy, and store them in water for later use.

[0015] 2) Preparation of polypyrrole-encapsulated silver nanowire-doped aerogel

[0016] 2.1) At room temperature, dimethylformamide (DMF) was added to cellulose acetate (CA) powder and stirred until a homogeneous and transparent solution system was formed. Then, stirring was continued at 70-75°C. During the stirring process, n-hexanol was added in small amounts several times and stirred continuously. After a homogeneous and transparent solution system was formed again, the polypyrrole-coated silver nanowires AgNWs@PPy obtained in step 1) were added and stirred thoroughly for 1.5-24 hours.

[0017] 2.2) After the reaction is complete, place the solution obtained in step 2.1) at room temperature for phase separation for at least 24 hours;

[0018] 2.3) Take out the phase-separated aerogel material and immerse it in anhydrous ethanol for displacement, shake it several times, each time for 6-12 hours, and then vacuum dry it at room temperature (a vacuum drying oven can be used) for at least 24 hours to obtain the target product polypyrrole-encapsulated silver nanowire-doped aerogel (CA / AgNWs@PPy).

[0019] Furthermore, in step 1), the AgNWs are synthesized using a simple single-pot method, as follows:

[0020] S1. Dissolve sodium chloride, ferric nitrate, polyvinylpyrrolidone, and silver nitrate in ethylene glycol to prepare four raw material solutions;

[0021] The mass ratio of sodium chloride, ferric nitrate, polyvinylpyrrolidone, and silver nitrate is 250-260: 80-82: 1040-1060: 1040-1060.

[0022] S2. Add the four raw material solutions prepared in S1 to ethylene glycol preheated to 130-140℃ for reaction;

[0023] S3. After the reaction is complete, wash the reactants with acetone and ultrapure water in sequence to obtain Ag NWs.

[0024] Furthermore, in step 1.1), the volume ratio of water to ethanol is 1:1;

[0025] The mass ratio of Ag NWs to Py monomers is 1:10;

[0026] In step 1.2), the amount of AgNO3 added is equal to the molar amount of pyrrole (Py) monomer;

[0027] In step 1.3), the precipitate is washed with an excess of deionized water and then stored in water. The duration of storage is not mandatory; it can be stored according to actual usage conditions, with the aim of facilitating use.

[0028] Further, in step 2.1), the mass ratio of cellulose acetate (CA) powder to AgNWs@PPy is 1:0.2 to 1;

[0029] The mass-to-volume ratio of cellulose acetate to dimethylformamide is 1:7, g / ml;

[0030] The mass-to-volume ratio of cellulose acetate to n-hexanol is 1:10.5, g / ml;

[0031] The dimethylformamide and n-hexanol mentioned above are the good solvent and the poor solvent for cellulose acetate, respectively. Adding the good solvent first to dissolve the cellulose, and then adding the poor solvent, can cause phase separation, which facilitates the formation of a porous structure.

[0032] Meanwhile, the present invention also provides the application of the above-mentioned polypyrrole-encapsulated silver nanowire-doped aerogel in the preparation of aerogel electrodes.

[0033] Based on the above applications, the present invention provides an aerogel electrode, which is obtained by immersing the above-mentioned polypyrrole-coated silver nanowire-doped aerogel in commercial conductive adhesive for at least 24 hours. After removal, it can be used for the measurement of electrophysiological signals.

[0034] Furthermore, the preparation method of the aerogel electrode is unique in that, based on the above-mentioned preparation method of polypyrrole-coated silver nanowire-doped aerogel, the following operation is performed:

[0035] The target product obtained in step 2) is polypyrrole-encapsulated silver nanowire-doped aerogel, which is then immersed in commercial conductive adhesive for at least 24 hours to obtain an aerogel electrode.

[0036] The above-mentioned aerogel electrodes are used as electrodes in flexible wearable devices.

[0037] A flexible wearable device, characterized by integrating the aforementioned aerogel electrodes.

[0038] The concept and principle of this invention:

[0039] Considering the inherent advantages of aerogels and silver nanowires, the research team of this invention chose to explore within the scope of silver nanowire-doped gels to address the issues of easy clustering of silver nanowires in the polymer matrix during molding and the susceptibility of silver nanowires to oxidation. The research team adopted a reverse-thinking approach, combining application requirements with the technical aspects needing improvement, to develop the technical solution of this invention:

[0040] First, silver nanowires were prepared using a seed crystal method, where silver was used as a seed crystal, ethylene glycol as a solvent and reducing agent, and PVP as a dispersant to synthesize AgNWs. Then, a polypyrrole coating was chemically polymerized onto the surface of the silver nanowires to protect them from oxidation and clustering, thereby imparting conductivity and antibacterial properties to the prepared electrode. Finally, AgNWs@PPy were dispersed in a mixed solution of cellulose acetate by stirring, and a porous aerogel was prepared using thermally induced phase separation to absorb commercial conductive adhesive and fabricate the electrode. This resulted in a long-lasting, antibacterial, flexible, and biocompatible aerogel electrode.

[0041] The beneficial effects of this invention are:

[0042] 1. This invention involves coating silver nanowires with a polypyrrole (PPy) coating. This coating not only isolates oxygen, slows down the oxidation process, and improves the structural stability of the silver nanowires (AgNWs have poor stability in oxidizing environments and their structure is easily destroyed), but also reduces the adhesion between silver nanowires, preventing cluster formation. Simultaneously, the PPy coating also improves conductivity; thus, polypyrrole-coated silver nanowires are prepared. On the other hand, a three-dimensional aerogel network is constructed from cellulose acetate. Stirring is used to ensure the polypyrrole-coated silver nanowires are uniformly distributed throughout the aerogel network, thereby improving conductivity and reducing contact resistance with the human body. This method perfectly solves the problems of easy clustering and oxidation during the molding of conductive polymers doped with silver nanowires, while possessing flexibility, antibacterial properties, moisture retention, and high conductivity. The polypyrrole-coated silver nanowire-doped aerogel electrode prepared by this method has promising application prospects in emerging industries such as wearable devices.

[0043] 2. The polypyrrole-coated silver nanowire-doped aerogel electrode synthesized in this invention exhibits good flexibility, low contact resistance, good moisture retention, good antibacterial properties, and good tissue compatibility. The flexible aerogel electrode prepared using green natural cellulose acetate is porous, capable of absorbing several times its own weight in water; simultaneously, the hydroxyl groups of cellulose acetate form hydrogen bonds with water molecules, further enhancing its water absorption and retention capacity. The polypyrrole-silver nanowires impart antibacterial properties to the flexible aerogel electrode, achieving a bactericidal rate of 97.8%. By inhibiting bacterial growth on the electrode surface, the electrode can be used on the skin for extended periods. Furthermore, the use of green cellulose as a synthetic raw material for the flexible aerogel electrode provides good tissue compatibility, which also contributes to its long-term use. Attached Figure Description

[0044] Figure 1 This is a flowchart illustrating the fabrication process of the aerogel electrode of the present invention.

[0045] Figure 2 The images show the microstructure of the products during the preparation of aerogels in this invention; where (a) and (d) are scanning electron microscope images of AgNWs, (b) and (e) are transmission electron microscope images of core-shell nanowires, and (c) is a transmission electron microscope image of aerogel doped with silver nanowires encapsulated in polypyrrole.

[0046] Figure 3 Water absorption rate test for each aerogel sample from S1 to S5;

[0047] Figure 4 Storage modulus of each aerogel sample (S1-S5) at room temperature (25℃) and body temperature (37℃);

[0048] Figure 5The figures show the contact impedance measurement results for each sample; where a represents the contact impedance of flexible aerogel electrodes S1-S5 in the 2mm thick sample, b represents the contact impedance of flexible aerogel electrodes S1-S5 in the 5mm thick sample, and c represents the contact impedance of flexible aerogel electrodes S1-S5 in the 7.5mm thick sample.

[0049] Figure 6 The contact resistance of aerogel electrodes under long-term use;

[0050] Figure 7 Verification of EEG signal acquisition (sample S1);

[0051] Figure 8 The in vitro sterilization rate of the aerogel electrode (sample S1);

[0052] Figure 9 Analysis of skin inflammatory response after 24 hours of use of aerogel electrode and commercial gold cup electrode (sample S1). Detailed Implementation

[0053] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments:

[0054] The raw materials used in this invention are as follows, and unless otherwise specified, all of them can be purchased commercially:

[0055] Ethylene glycol (EG), sodium chloride (NaCl), ferric nitrate (Fe(NO3)3), polyvinylpyrrolidone (PVP), non-hydrated ferric nitrate (Fe(NO3)3, 99.999%), silver nitrate (AgNO3), acetone, Milli-Q water, pyrrole, cellulose acetate, N,N-dimethylformamide (DMF), 1-Hexanol, and ethanol.

[0056] like Figure 1 As shown, this invention first prepares silver nanowires, then uses the silver nanowires as templates to prepare polypyrrole-coated silver nanowires (AgNWs@PPy), and further prepares a flexible, antibacterial, and moisturizing aerogel (CA / AgNWs@PPy) doped with polypyrrole-coated silver nanowires. Finally, the flexible aerogel is immersed in commercial conductive adhesive to prepare a flexible, antibacterial, and moisturizing aerogel electrode.

[0057] Example 1

[0058] A method for preparing a polypyrrole-encapsulated silver nanowire-doped aerogel is as follows:

[0059] 1) Preparation of silver nanowires:

[0060] First, place 140 mL of ethylene glycol (EG) in a three-necked flask and preheat it at 140 °C for 1 hour using a flow condenser;

[0061] Then, 257 mg of sodium chloride (NaCl), 81 mg of ferric nitrate (Fe(NO3)3), 1050 mg of polyvinylpyrrolidone (PVP) and 1050 mg of silver nitrate (AgNO3) were dissolved in EG to prepare four raw material solutions.

[0062] The four raw material solutions were then added to the preheated EG and reacted for 4 hours. After the reaction was completed, the resulting mixture was washed with acetone and ultrapure water to obtain silver nanowires (AgNWs).

[0063] 2) Preparation of polypyrrole-coated silver nanowires:

[0064] 0.4 mg of the AgNWs obtained in step 1) were dispersed in a mixed solution of water and ethanol (volume ratio 1:1) and 4 mg of Py monomer were mixed and stirred at room temperature. Then, AgNO3 solution (with the same molar amount as Py monomer) was added to the mixed solution. Mixing and stirring were continued for 3 hours, and then the solution was allowed to stand overnight. The precipitate was filtered and washed with excess deionized water to obtain polypyrrole-encapsulated silver nanowires AgNWs@PPy, which were then stored in water for 24 hours.

[0065] 3) Preparation of polypyrrole-encapsulated silver nanowire-doped aerogel:

[0066] Take 2g of cellulose acetate (CA) powder and place it in a 100mL round-bottom flask. At room temperature, add 14mL of dimethylformamide (DMF) and stir vigorously until a homogeneous and transparent solution is formed. Then place it in a 75℃ oil bath and continue stirring. During the stirring process, add 21mL of n-hexanol in small amounts several times and continue stirring until a homogeneous and transparent solution system is formed again. Then add 0.4g of AgNWs@PPy obtained in step 2) and stir thoroughly for 1.5h. Draw the resulting solution into a 2mL syringe (or use a centrifuge tube or other equipment to place the mixed solution and help it stand and form). Place it at room temperature (20℃) for phase separation for 24h. Take out the aerogel material and soak it in anhydrous ethanol for displacement, shake it 3 times, 12h each time. Vacuum dry it in a vacuum drying oven at room temperature (30℃) for 24h to obtain polypyrrole-coated silver nanowire-doped aerogel CA / AgNWs@PPy.

[0067] To test the product performance under different ratios of CA and AgNW@PPy, this invention also conducted experiments with different sample feeds, as shown in Table 1, under the same other process conditions, and tested the storage modulus and impedance. S1 is 2g of cellulose acetate and 0.4g of AgNW@PPy.

[0068] Table 1

[0069]

[0070] 4) The polypyrrole-coated silver nanowire-doped aerogel CA / AgNWs@PPy obtained in step 3) is immersed in commercial conductive adhesive for at least 24 hours to prepare an aerogel electrode.

[0071] To further verify the effectiveness of the present invention, the following performance tests were conducted:

[0072] I. Microscopic morphology

[0073] The microstructures of the intermediate and target products were characterized using scanning electron microscopy (SEM) (ZEISS Geini 300) and transmission electron microscopy (TEM) (Talos F200X).

[0074] Figure 2 Images (a) and (d) are scanning electron microscope (SEM) images of AgNWs. It can be seen that the AgNWs prepared in step 1) are very thin, with a length of approximately 15 μm and an average width of approximately 80-200 nm, and can be uniformly dispersed in pure water. Images (b) and (e) are transmission electron microscope (TEM) images of core-shell AgNWs@PPy. It can be seen that the core-shell AgNWs@PPy with a polypyrrole coating has an increased width of approximately 300 nm compared to the original AgNWs, and the coating thickness can be adjusted according to the amount of pyrrole added. Image (c) shows a polypyrrole-encapsulated silver nanowire-doped aerogel. It can be seen that cellulose acetate crosslinking forms the final three-dimensional gel network structure, with AgNWs@PPy doped within it.

[0075] II. Water Absorption Performance

[0076] The water absorption rate of aerogel samples S1-S5 was calculated by determining the mass change before and after water absorption. All samples maintained high water absorption capacity, with sample S1 exhibiting the highest water absorption rate. Figure 3 ).

[0077] III. Mechanical Properties

[0078] The mechanical properties of the gels were measured at 25°C and 37°C using a dynamic thermomechanical analyzer (NETZSCH DMA 242E) to obtain the storage modulus of each sample.

[0079] Figure 4 The effect of AgNWs@PPy on the storage modulus of the manufactured samples was shown. Five samples, S1-S5, were tested under the same conditions. It is clear that increasing the percentage of AgNWs@PPy leads to a higher storage modulus, with a maximum value approaching 3 MPa. This can be attributed to the higher strength of AgNWs@PPy as a filler to improve the strength of the composite. It is also clear that increasing the percentage of cellulose decreases the storage modulus, thus reducing the stiffness of the sample. This can help improve the flexibility of the sample because the strain is higher under the same stress, such as... Figure 4 As shown, the storage modulus of the samples decreases with the percentage of cellulose, with the sample made from the largest amount of cellulose (i.e., sample S1) having a minimum storage modulus of approximately 1.0 MPa. In fact, samples with lower cellulose content exhibit greater stiffness. This behavior of stiffness and strength may be due to the relatively stronger physical entanglement in samples with higher AgNWs@PPy content. That is, the higher the mass percentage of cellulose acetate, the better the flexibility of the aerogel electrode; the higher the mass percentage of AgNWs@PPy, the greater the stiffness.

[0080] Overall, the mechanical properties of the fabricated aerogels were thoroughly investigated throughout the test results under the influence of various parameters (e.g., cellulose acetate and AgNWs@PPy), which is beneficial for the mechanical properties of custom-fabricated electrodes.

[0081] IV. Electrode Skin Contact Resistance

[0082] The contact impedance of the aerogel electrodes was measured using an impedance testing system (WK 1J65120BD2). Electrical characterization was performed on five different flexible aerogel electrode samples with thicknesses of 2 mm, 5 mm, and 7.5 mm. Figure 5 The impedance characteristics of flexible aerogel electrodes fabricated by immersing the corresponding samples in conductive adhesive were characterized. Different electrode materials exhibited similar electrical behavior. The impedance values ​​of the fabricated flexible aerogel electrode samples ranged from 1 kΩ to 100 kΩ, significantly less than 200 kΩ. Therefore, all five flexible aerogel electrode samples possessed relatively low impedance ranges, making them suitable for electrophysiological signal detection.

[0083] V. Moisturizing properties

[0084] The contact impedance changes of commercial electrodes and aerogel electrodes were measured over 24 hours using an impedance testing system (WK 1J65120BD2). After 24 hours, the contact impedance of the aerogel electrode was still less than 200 kΩ. Figure 6 Commercial electrodes have reached the MΩ level, which is not suitable for measuring electrophysiological signals.

[0085] VI. Sensing Performance

[0086] like Figure 7 As shown, to compare EEG signals in the forehead region, flexible AgNWs@PPy-CA aerogel electrodes were placed at Fp1 and Fp2 according to the 10-20 system. Commercial electrodes were placed approximately 3 cm away from Fp1 and Fp2, and additional commercial electrodes were placed on both ears of the subject as reference electrodes. Figure 7 The left image shows 5-second long EEG signals at Fp1 and Fp2 from the flexible AgNWs@PPy-CA aerogel electrode and the commercial electrode, respectively. Two similar blink potentials were observed simultaneously from both electrodes. To compare EEG signals in hairy regions, the flexible AgNWs@PPy-CA aerogel electrodes were placed on the heads of subjects O1 and O2 according to the 10-20 system. The commercial electrode was placed approximately 3 cm away from O1 and O2, and another commercial electrode was placed on each ear as a reference electrode. Data from all channels were recorded in parallel using OpenBCI Cyton. EEG signals were collected and compared between the commercial electrode and the flexible AgNWs@PPy-CA aerogel electrode. Figure 7 The right figure shows the electrode locations and the results of raw EEG signals measured at the forehead (Fp1) and hair follicle (O1), respectively. The correlation coefficients between the EEG signals from the paired electrodes are 0.94223 at the forehead and 0.91326 at the hair follicle. Therefore, it can be shown that the EEG signal quality of the flexible aerogel electrode prepared by this invention is very close to that of commercial electrodes, and it has good application prospects.

[0087] VII. Antibacterial properties

[0088] exist Figure 8 In the study, numerous colonies were observed on plates using commercial electrodes and CA aerogel assemblies. Conversely, the number of colonies was significantly reduced on plates using aerogel electrodes. Figure 8 As shown, the bacterial log number of Escherichia coli in the aerogel electrode was reduced to 1.72±0.33 (sterilization rate of over 97.8%). It can be seen that the introduction of AgNWs provides the aerogel electrode with significant sterilization efficiency. The excellent antibacterial performance of the aerogel electrode is attributed to the oxidation of AgNWs to form Ag ions. Silver nanomaterials have good antibacterial properties. Compared with silver nanoparticles, silver nanowires have a longer release time and are conducive to long-term antibacterial applications.

[0089] 8. Biocompatibility

[0090] Commercial electrodes and aerogel electrodes were applied to the backs of mice for 24 hours, and inflammation analysis was performed on the corresponding skin areas. The results showed that the underlying skin tissue of the commercial electrode exhibited a large accumulation of neutrophils, a typical symptom of inflammation and infection (e.g., ...). Figure 9(As shown). H&E staining results indicated that the aerogel electrode avoided inducing severe inflammation, a fact also confirmed by images of inflammatory cytokines: TNF-α and IL-6 in macrophages. Therefore, the aerogel electrode, after 24 hours of application to the skin, elicited a less inflammatory response than the commonly used commercial gold cup electrode.

[0091] In summary, through a series of analyses and tests on mechanical properties, microstructure, conductivity, water absorption, and moisturizing properties, it can be determined that the aerogel electrode prepared by this invention possesses excellent moisturizing properties, high conductivity, and stretchability. It can be applied in the integration of flexible wearable devices. It utilizes porous aerogel materials to adsorb a large amount of conductive adhesive; the aerogel prepared using cellulose acetate imparts good flexibility, improving user comfort; and the use of doped AgNWs@PPy further reduces contact resistance and improves the electrode's sterilization rate, thereby extending the electrode's lifespan, demonstrating excellent application prospects.

[0092] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the scope of the technology disclosed in the present invention, and such modifications or substitutions should all be covered within the scope of protection of the present invention.

Claims

1. The application of a polypyrrole-coated silver nanowire-doped aerogel in the preparation of flexible aerogel EEG electrodes, characterized in that: the aerogel comprises a three-dimensional aerogel network obtained by physical cross-linking of cellulose acetate through static interaction, and polypyrrole-coated silver nanowires uniformly doped in the three-dimensional aerogel network. The average width of the silver nanowires is 80-200 nm, and the average width of the polypyrrole-coated silver nanowires is 200-400 nm; the thickness of the polypyrrole coating is 120-200 nm. The method for preparing the aerogel includes the following steps: 1) Preparation of polypyrrole-coated silver nanowires 1.1) Silver nanowires (Ag NWs) were dispersed in a mixed solution of water and ethanol, and then mixed and stirred with pyrrole monomer at room temperature; the mass ratio of Ag NWs to pyrrole monomer was 1:

10. 1.2) Add AgNO3 solution to the mixed solution obtained in step 1.1), continue stirring for 3-6 h, and then let stand for at least 24 h; 1.3) After the reaction is complete, filter and wash the precipitate to obtain polypyrrole-encapsulated silver nanowires AgNWs@PPy, and store them in water for later use. 2) Preparation of polypyrrole-encapsulated silver nanowire-doped aerogel 2.1) At room temperature, dimethylformamide was added to cellulose acetate powder and stirred until a homogeneous and transparent solution system was formed. Then, stirring was continued at 70-75 °C. During the stirring process, n-hexanol was added in small amounts several times and stirred continuously. After a homogeneous and transparent solution system was formed again, the polypyrrole-coated silver nanowires AgNWs@PPy obtained in step 1) were added and stirred thoroughly for 1.5-24 h. The mass ratio of the cellulose acetate powder to AgNWs@PPy is 1:0.2~1; The mass-to-volume ratio of cellulose acetate to dimethylformamide is 1:7, g / ml; The mass-to-volume ratio of cellulose acetate to n-hexanol is 1:10.5, g / ml; 2.2) After the reaction is complete, place the solution obtained in step 2.1) at room temperature for phase separation for at least 24 h; 2.3) The aerogel material after phase separation was taken out and immersed in anhydrous ethanol for displacement, shaken multiple times for 6-12 h each time, and then vacuum dried at room temperature for at least 24 h to obtain the target product, polypyrrole-encapsulated silver nanowire-doped aerogel CA / AgNWs@PPy.

2. The application according to claim 1, characterized in that: In step 1), the preparation method of the AgNWs is as follows: S1. Dissolve sodium chloride, ferric nitrate, polyvinylpyrrolidone, and silver nitrate in ethylene glycol to prepare four raw material solutions; The mass ratio of sodium chloride, ferric nitrate, polyvinylpyrrolidone, and silver nitrate is 250-260: 80-82: 1040-1060: 1040-1060. S2. Add the four raw material solutions prepared in S1 to ethylene glycol preheated to 130-140 ℃ for reaction; S3. After the reaction is complete, wash the reactants with acetone and ultrapure water in sequence to obtain Ag NWs.

3. The application according to claim 1 or 2, characterized in that: In step 1.1), the volume ratio of water to ethanol is 1:1; In step 1.2), the amount of AgNO3 added is equal to the molar amount of pyrrole monomer; In step 1.3), the precipitate is washed with an excess of deionized water.

4. A flexible aerogel EEG electrode, characterized in that: The polypyrrole-encapsulated silver nanowire-doped aerogel used in the application of claim 1 is obtained by immersing it in a commercially available conductive adhesive for at least 24 hours.

5. The method for preparing the flexible aerogel EEG electrode according to claim 4, characterized in that, Based on the method for preparing polypyrrole-encapsulated silver nanowire-doped aerogel as described in claim 1, the following steps are performed: The target product obtained in step 2) is polypyrrole-encapsulated silver nanowire-doped aerogel, which is then immersed in commercial conductive adhesive for at least 24 hours to obtain an aerogel electrode.

6. The application of the flexible aerogel EEG electrode of claim 4 as an electrode in a flexible wearable device.

7. A flexible wearable device, characterized in that: It integrates the flexible aerogel EEG electrode as described in claim 4.

Citation Information

Patent Citations

  • Cellulose triacetate aerogel and preparation method

    CN104130444A

  • Lightweight high-performance electromagnetic shielding material and preparation method thereof

    CN115093611A